The status, distribution and habitat requirements of the grey rhebuck, Pelea capreolus, (Forster, 1790) in the Orange Free State - Ferreira, Niel Andre (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1983.